الضرورة الشعرية عند النقاد حتى نهاية القرن الرابع الهجري وآراء المحدثين فيها - عوض سامي; يحيا مالك; زهيري كسرى (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
This research studies the poetic necessity according to the critics who were interested in poetry, and wrote criticized books chose between poetry and poets , and classified poetry into section , depending on meaning and pronunciation . Critics emphasized the unique nature of poetry ,this uniqueness made the poets question what was against then rules making apologies for it to keep it accepted . Critics looked at poetry as another level of expression and approved it with terms and conditions , such as / shame / judgement and poetry phenomena , such of it according to necesseties , critics had different views about necessities , some refused it , and described as ugliness that fades away by words water , while others approved it . Whatever opinion have the critics about necessities , it is aphenomenon that took their attention , some wrote whole books , and others chapters . In most cases , no one called it as mistake , and the lasting effect of poetry that has necessities keep it approved . يتناول البحث الضرورة الشعرية عند أهمّ النقاد الذين اهتموا بالشعر، وألفوا فيه كتباً ، وأطلقوا عليه أحكاماً، وفاضلوا بين الأشعار ، وصنّفوها معتمدين اللفظ والمعنى في أحكامهم . أكد النقاد الطبيعة الخاصة للشعر ، وهذه الخصوصية جعلت النحاة يقفون أمام ما خالف قواعدهم ، يلتمسون الأعذار لإبقائه في دائرة القبول ، أما النقاد فنظروا إلى الشعر على أنه مستوى آخر في التعبير واستحسنوه ، لكنهم وضعوا للشعر معاييرَ وأطلقوا حكم / العيب / على بعض الظواهر في الأشعار ، ومن بعض العيوب ما صنّفه النحاة ضرائر . اختلف النقاد في مواقفهم من الضرائر ، فمنهم من رفضها ووصفها بالقبح الذي يُذهب بماء الكلام ، ومنهم من استحسن بعضها ، ومهما يكن من أمر النقاد وموقفهم من الضرائر ، فإنها ظاهرة نالت اهتمامهم ، فمنهم من ألّف فيها كتاباً مستقلاً ، ومنهم من أفرد لها فصولاً من كتاب ، وفي أغلب الأحكام لم يُطلق عليها صفة الخطأ ، وإنّ خلود الأبيات التي تحمل ضرورات يبقيها في دائرة الاستحسان .